Infliximab trough levels may predict sustained response to infliximab in patients with Crohn's disease - Bortlik, Martin; Duricova, Dana; Malickova, Karin; Machkova, Nadezda; Bouzkova, Eva; Hrdlicka, Ludek; Komarek, Arnost; Lukas, Milan (Journal of Crohn's & colitis, 2013)
BACKGROUND AND AIMS: Over 10% of Crohn's disease (CD) patients annually lose response to infliximab. Infliximab trough levels (TL), concomitant immunosuppressants and endoscopic healing were proposed as predictors of favourable infliximab outcome. We assessed infliximab TL measured after induction therapy as predictors of sustained clinical response. Furthermore, we tried to identify other predictors of long-term benefit of infliximab therapy. METHODS: We included CD patients treated with infliximab between October 2007 and March 2010 who responded to 3-dose induction followed by maintenance therapy and in whom blood samples taken at treatment week 14 or 22 were available in blood bank. Sustained response to infliximab was defined as absence of treatment failure due to loss of response or drug intolerance. RESULTS: Eighty four patients were included. Sustained response to infliximab was observed in 47 (56%) patients during a median follow-up of 25 months (14-37). Infliximab TL>3μg/ml were associated with a decreased risk of treatment failure (HR 0.34; 95% CI: 0.16-0.75), whereas the presence of antibodies against infliximab and need for corticosteroids increased this risk (HR 4.34; 95% CI: 1.51-12.5 and HR 2.49, 95% CI: 1.08-5.73, respectively). No impact of concomitant thiopurines was observed, although patients receiving thiopurines had higher infliximab TL than those without immunomodulators (5.51 vs. 0.71μg/ml; p=0.01). CONCLUSION: During a median follow up of 2 years sustained response to infliximab was observed in slightly more than half of CD patients. Infliximab TL>3μg/ml at the start of maintenance regime were predicative of sustained response to infliximab.
Keywords: ROC Curve; Infliximab; IBD; Humans; hormony kůry nadledvin; anti-infliximab antibodies; trough level; lidé středního věku; C-reaktivní protein; Predictive Value of Tests; infliximab; Antibodies, Monoclonal; Female; mladý dospělý; dospělí; udržovací chemoterapie; inflammatory bowel disease.; Time Factors; Crohn Disease; Sustained response; lidé; antiflogistika nesteroidní; Anti-Inflammatory Agents, Non-Steroidal; TNF-α; Predictors; imunosupresiva; časové faktory; Maintenance Chemotherapy; Crohn's disease; Adult; Immunosuppressive Agents; TL; CD; Follow-Up Studies; ženské pohlaví; Male; Middle Aged; prediktivní hodnota testů; protilátky; tumour necrosis factor alpha; Adolescent; ATI; Crohnova nemoc; Antibodies; monoklonální protilátky; Young Adult; ROC křivka; Adrenal Cortex Hormones; mužské pohlaví; Treatment Failure; kombinovaná farmakoterapie; C-Reactive Protein; neúspěšná terapie; následné studie; Drug Therapy, Combination; mladiství